Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Show that $(n+\sqrt{n^2 -1})^k$ will always be of the form$ (t+\sqrt{t^2 -1})$ where $n$, $k$, $t$ are natural numbers

share|improve this question
2  
What have you tried? –  Mark Bennet Aug 3 '12 at 8:30
    
Try to prove it by induction –  Norbert Aug 3 '12 at 8:56
    
$(2+\sqrt3)^1 = (2+\sqrt[]{2^2-1})$ –  Rajesh K Singh Aug 3 '12 at 9:00
    
$(3+\sqrt8)^1=(3+\sqrt[]{3^2-1})$,$(3+\sqrt8)^2=(17+\sqrt[]{17^2-1})$ –  Rajesh K Singh Aug 3 '12 at 9:03
2  
It would be useful to know some context, and whether this is homework, and where the problem comes from and why it is interesting. There is a neat way of looking at this, but it would be a shame to be given a 'magic' solution out of context because you won't then be able to apply the same idea to a different problem. –  Mark Bennet Aug 3 '12 at 9:04
show 7 more comments

6 Answers

up vote 4 down vote accepted

I enjoyed working this out-cool question man. Here's a straightforward inductive proof:

I'm writing $c$ instead of $n$.

Inductively assume $(c + \sqrt{c^2 - 1})^k = a + b \sqrt{c^2 - 1}$, where $b^2(c^2 - 1) = a^2 - 1$ (the base case is clear). That is, not only can you write it as $t + \sqrt{t^2 - 1}$, but also $t^2 - 1$ is a square times $c^2 - 1$ (I guessed this by working out the first $k$'s for $c =2,3$).

Now to see $k \Rightarrow k+1$, we have $$(c + \sqrt{c^2 - 1})^{k+1} = (a + b \sqrt{c^2 - 1})(c + \sqrt{c^2 - 1}) $$$$= (ac + b(c^2 - 1)) + (a + cb)\sqrt{c^2 - 1}$$It suffices to check that $$(ac + b(c^2 - 1))^2 - 1 = (a + cb)^2(c^2 - 1)$$Expanding both sides gives $$c^2 a^2 + 2c(c^2 - 1)ab + (c^2 - 1)^2 b^2 - 1 = (c^2 - 1)a^2 + 2c(c^2 - 1)ab + c^2(c^2 - 1)b^2$$Cancelling the $ab$ terms, pulling the $a^2$ term to the LHS, and the $b^2$ terms to the RHS, we get $$a^2 - 1=b^2(c^2 - 1) $$our inductive hypothesis.

share|improve this answer
    
thanks for the hints. –  Rajesh K Singh Aug 3 '12 at 14:09
    
is it square times $b\sqrt[]{c^2-1}$ –  Rajesh K Singh Aug 3 '12 at 14:39
    
hmm, I guess mean that $\sqrt{t^2 - 1}$ can always be simplified to $b \sqrt{c^2 - 1}$, i.e. that $t^2 - 1 = b^2(c^2 - 1)$. For example, as you computed, for powers of $(2 + \sqrt{3})$, for $k=2$ you get $7 + 4\sqrt{3} = 7 + \sqrt{7^2 - 1}$, and for $k=3$ you get $26 + 15\sqrt{3} = 26 + \sqrt{26^2 - 1}$ –  uncookedfalcon Aug 3 '12 at 21:37
add comment

Let $\sqrt {n^2-1}=\alpha$

Then $(n+\alpha)(n-\alpha)=1$ and it is easy to see (prove by induction) that $(n+\alpha)^k = t+u\alpha \text{ and } (n-\alpha)^k = t-u\alpha$ with $t$ and $u$ integers so: $$1=(n+\alpha)^k(n-\alpha)^k = (t+u\alpha)(t-u\alpha)= t^2-u^2\alpha^2 $$

So $$u\alpha = \sqrt{t^2-1} \text{ and } (n+\alpha)^k=t+\sqrt{t^2-1}$$

share|improve this answer
    
thanks for the clue –  Rajesh K Singh Aug 3 '12 at 14:10
add comment

First of all, notice that if $n$ is an integer and $a = n + \sqrt{n^2-1}$, then $n = \frac{1}{2}(a+\frac{1}{a})$. Next notice that the direction of implication can be reversed here, i.e. if $\frac{1}{2}(a+\frac{1}{a})$ is an integer then a can be written in the form $n + \sqrt{n^2-1}$ where $n$ is an integer by setting $n = \frac{1}{2}(a+\frac{1}{a})$.

With this in mind, we simply have to prove that if $\frac{1}{2}(a+\frac{1}{a})$ is an integer then so is $\frac{1}{2}(a^k+\frac{1}{a^k})$ for any integer $k$. This can be easily seen by induction on $k$ using the binomial expansion of $(a+\frac{1}{a})^k$ and the symmetry of the binomial coefficients.

EDIT:

To clarify the second part, $$\left(a+\frac{1}{a}\right)^k = \left(a^k+\frac{1}{a^k}\right) + \sum_{i=1}^{\lfloor{k/2}\rfloor}{k \choose i} + (\text{if $k$ even}){k \choose k/2}$$

LHS is $k$th power of even number so even. All but first term in RHS are even (by induction hypothesis and fact that central binomial coefficient is even). So $(a^k+\frac{1}{a^k})$ must also be even.

share|improve this answer
add comment

The roots of $x+\frac1x=2n$ are $x_n=n+\sqrt{n^2-1}$ and $1/x_n=n-\sqrt{n^2-1}$.

If we can show that $$ x_n^k+1/x_n^k=2m_{n,k}\tag{1} $$ (that is, an even integer), then we get the form we want: $$ x_n^k=m_{n,k}+\sqrt{m_{n,k}^2-1}\tag{2} $$ Initial Case: for $k=1$, obviously, $x_n^1+1/x_n^1=2n$.

Inductive Case: suppose that $(1)$ holds for all $j<k$, that is, $x_n^j+1/x_n^j=2m_{n,j}$. Then, $$ \begin{align} (2n)^k &=\left(x_n+1/x_n\right)^k\\ &=x_n^k+1/x_n^k+\sum_{j=1}^{k-1}\binom{k}{j}x_n^{k-2j}\\ &=x_n^k+1/x_n^k+\left\{\begin{array}{} \binom{k}{k/2}+\sum_{j=1}^{k/2-1}\binom{k}{j}(x_n^{k-2j}+1/x_n^{k-2j})&\mbox{if $k$ is even}\\ \sum_{j=1}^{(k-1)/2}\binom{k}{j}(x_n^{k-2j}+1/x_n^{k-2j})&\mbox{if $k$ is odd} \end{array}\right.\\ &=x_n^k+1/x_n^k+\left\{\begin{array}{} \binom{k}{k/2}+2\sum_{j=1}^{k/2-1}\binom{k}{j}m_{n,k-2j}&\mbox{if $k$ is even}\\ 2\sum_{j=1}^{(k-1)/2}\binom{k}{j}m_{n,k-2j}&\mbox{if $k$ is odd} \end{array}\right.\tag{3} \end{align} $$ When $k$ is even, $\binom{k}{k/2}$ has as many factors of $2$ as there are $1$-bits in the binary representation of $k$ (that is, at least $1$). Therefore, since $(2n)^k$, $\binom{k}{k/2}$ (if $k$ is even), and $2\sum\binom{k}{j}m_{n,k-2j}$ are all even, $(3)$ says that $x_n^k+1/x_n^k$ is even, which validates $(1)$.


Recursion for $m_{n,k}$:

Start with $m_{n,1}=n$, then $$ m_{n,k}=2^{k-1}n^k-\left\{\begin{array}{} \frac12\binom{k}{k/2}+\sum_{j=1}^{k/2-1}\binom{k}{j}m_{n,k-2j}&\mbox{if $k$ is even}\\ \sum_{j=1}^{(k-1)/2}\binom{k}{j}m_{n,k-2j}&\mbox{if $k$ is odd} \end{array}\right. $$

share|improve this answer
add comment

Hint $\rm\ \alpha = n\! +\! \sqrt{n^2\!-\!1}\:$ has norm $\rm\,N(\alpha) = \alpha\alpha' = n^2\!-(n^2\!-\!1) = 1,\:$ so $\rm\:N(\alpha^n) = N(\alpha)^n = 1.\:$

Conversely, quadratic numbers of norm $1$ have this form: $\rm\: 1 = (a\!+\!bw)(a\!-\!bw) = a^2\! -\! b^2 w^2,\:$ so $\rm\: b^2 w^2 = a^2\!-\!1\:\Rightarrow\: bw = \sqrt{a^2\!-\!1}\:\Rightarrow\:a+bw = a+\sqrt{a^2-1},\:$ by $\rm\:w^2 > 0,\,$ and wlog $\rm\,b\ge 0.$

share|improve this answer
add comment

Let, $$f(k)=(2+\sqrt[]{2^2-1})^k$$ -------(1)

consider $k=1$

$$f(1)=(2+\sqrt[]{2^2-1})^1$$

i.e. $$f(1)=(2+\sqrt[]{2^2-1})=\frac{1}{2-\sqrt[]{2^2-1}}$$

consider $k=2$

$$f(2)=(2+\sqrt[]{2^2-1})^2$$

i.e. $$f(2)=(4+(2^2-1)+4\sqrt[]{2^2-1})$$

i.e. $$f(2)=(7+4\sqrt[]{2^2-1})$$

i.e. $$f(2)=(7+\sqrt[]{(4^2)(2^2-1)})$$

i.e. $$f(2)=(7+\sqrt[]{7^2-1})=\frac{1}{7-\sqrt[]{7^2-1}}$$ Assume $f(n)$ holds for $k=n$

i.e. $$f(n)=(2+\sqrt[]{2^2-1})^n=(t+\sqrt[]{t^2-1})=(a+b\sqrt[]{3})$$ -------(2)

where a and b are natural numbers

i.e. $$f(n)=(2+\sqrt[]{2^2-1})^n=(t+\sqrt[]{t^2-1})=(a+\sqrt[]{3b^2})$$

for the assumption to hold, $$3b^2 = a^2-1$$ -------(3)

consider $k=n+1$

i.e. $$f(n+1)=(2+\sqrt[]{2^2-1})^{n+1}=(t+\sqrt[]{t^2-1})(2+\sqrt[]{2^2-1})$$

we also have, $$f(n+1) =(a+b\sqrt[]{3})(2+\sqrt[]{3})$$

where a and b are natural numbers

i.e. $$f(n+1)=(2a+3b)+(a+2b)\sqrt[]{3}$$ -------(4)

i.e. $$f(n+1)=(2a+3b)+\sqrt[]{3(a+2b)^2}$$

i.e. $$f(n+1)=(2a+3b)+\sqrt[]{3(a^2+4b^2+4ab)}$$

i.e. $$f(n+1)=(2a+3b)+\sqrt[]{3a^2+12b^2+12ab)}$$

i.e. $$f(n+1)=(2a+3b)+\sqrt[]{3a^2+12b^2+12ab + (a^2-a^2) + (3b^2-3b^2)}$$ -------(5)

i.e. $$f(n+1)=(2a+3b)+\sqrt[]{(3a^2+12b^2+12ab +a^2) -a^2 + (3b^2-3b^2)}$$

i.e. $$f(n+1)=(2a+3b)+\sqrt[]{(4a^2+12b^2+12ab) + (3b^2-3b^2) -a^2}$$

i.e. $$f(n+1)=(2a+3b)+\sqrt[]{(4a^2+12b^2+12ab) + (-3b^2+3b^2) -a^2}$$

i.e. $$f(n+1)=(2a+3b)+\sqrt[]{(4a^2+12b^2+12ab -3b^2) +3b^2 -a^2}$$

i.e. $$f(n+1)=(2a+3b)+\sqrt[]{(4a^2+9b^2+12ab) + (3b^2 -a^2)}$$

i.e. $$f(n+1)=(2a+3b)+\sqrt[]{(2a+3b)^2 + (3b^2 -a^2)}$$ -------(6)

by careful observation, using expressions (3) and (6) we have $$f(n+1)=(2a+3b)+\sqrt[]{(2a+3b)^2 + (a^2 -1 -a^2)}$$

i.e. $$f(n+1)=(2a+3b)+\sqrt[]{(2a+3b)^2 -1 + (a^2-a^2)}$$

i.e. $$f(n+1)=(2a+3b)+\sqrt[]{(2a+3b)^2 -1}$$ which is indeed of the form $$f(n+1)=(t+\sqrt[]{t^2-1})$$ where $t=(2a+3b)$

share|improve this answer
    
yeah man exactly! (well, I didn't check all the steps, but I think your argument is what I was thinking as well) –  uncookedfalcon Aug 3 '12 at 21:39
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.